Formation of Organizational Capacity among Students - Jakhona Karimova O‘ktamjon Qizi (International Journal on Integrated Education, 2021)
Organizational ability is a person's ability to organize. A person's ability to be a leader largely depends on the development of his organizational and communicative qualities. A leader is a person who controls people, organizes them. The leader leads as long as he is in the given social role. The leader and the organizer are similar in fulfilling their roles, but the leader differs from the organizer in that he has more authority. For example, the leader of the youth parties, the leader of the youth movement. The following article looks into the formation of organizational skills and its importance in school life.